Isi Piringku on the prevention of stunting in pregnant women - Salsa Billa Nurfadillah; Lucky Septian Ruswandi (Universitas Pendidikan Indonesia, 2024)
Isi Piringku emphasizes the importance of balance between staple foods, vegetables, side dishes, and fruits, with specific measurements to ensure optimal nutritional intake. This community service aims to evaluate the influence of nutrition, represented by the Isi Piringku concept, on pregnant women's health and their fetuses' development. In this context, the community service conducted assesses how the implementation of a diet based on Isi Piringku can contribute to fetal health and the prevention of stunting, a form of chronic malnutrition that occurs in the first 1000 days of life, starting from when the fetus is in the womb. The method used in this community service is qualitative-participatory. This method elaborates the learning process with instructors acting as researchers and observers working with target subjects. Learning uses a group discussion and quiz model. The results of the community service show that pregnant women who follow the Isi Piringku guide tend to have a more balanced nutritional intake, which contributes to more optimal fetal growth and development and reduces the risk of stunting. These findings emphasize the importance of nutritional education and implementing the Isi Piringku concept for pregnant women to promote a healthier and better quality generation. Abstrak Isi Piringku menekankan pentingnya keseimbangan antara makanan pokok, sayur, lauk pauk, dan buah, dengan takaran yang spesifik untuk memastikan asupan nutrisi yang optimal. Pengabdian ini bertujuan untuk mengevaluasi pengaruh gizi yang diwakili oleh konsep Isi Piringku terhadap kesehatan ibu hamil dan perkembangan janinnya. Dalam konteks ini, pengabdian yang dilakukan menilai bagaimana penerapan pola makan berdasarkan Isi Piringku dapat berkontribusi pada kesehatan janin dan pencegahan stunting, suatu bentuk malnutrisi kronis yang terjadi dalam 1000 hari pertama kehidupan, dimulai sejak janin berada di kandungan. Metode yang digunakan pada pengabdian ini yaitu kualitatif-partisipatoris. Metode ini mengelaborasi proses belajar aktual dengan instruktur bertindak sebagai peneliti dan observator bekerja sama dengan subjek sasaran. Pembelajaran menggunakan model diskusi grup dan quiz. Hasil pengabdian menunjukkan hasil bahwa ibu hamil yang mengikuti panduan Isi Piringku cenderung memiliki asupan nutrisi yang lebih seimbang, yang berkontribusi pada pertumbuhan dan perkembangan janin yang lebih optimal, serta mengurangi risiko terjadinya stunting. Temuan ini menegaskan pentingnya edukasi gizi dan penerapan konsep Isi Piringku bagi ibu hamil demi generasi yang lebih sehat dan berkualitas. Kata Kunci: gizi; ibu hamil; isi piringku; stunting